Metastatic prostate adenocarcinoma presenting as supraclavicular lymphadenopathy: a report of two cases - Davarci, Mürsel; Gokce, Ahmet; Guven, E. Oguz; Yalcinkaya, Fatih R.; Esen, Hasan; Sevinc, Alper (Contemporary Oncology/Współczesna Onkologia, 2012)
Clinical examination is very important in the practice of medicine. In patients presenting with a supraclavicular mass, a number of diseases including cancer should be ruled out. Two patients who presented with a bulky left supraclavicular mass were evaluated. Their medical history revealed complaints attributed to lower urinary tract infection. We performed histopathological examination of the lymph nodes with radiological evaluation of the thorax and abdomen. The final diagnoses were prostate cancer in both patients. It should always be kept in mind that prostate cancer is the most frequent cancer in elderly men, and although very unusual, the presenting finding can be cervical or supraclavicular lymphadenopathy; thus clinicians should be aware of urological examinations in such cases.